Trends in Educational Research in Colombia: Contributions for a Comprehensive, Historical and Cultural Framework - González-López, José Jair (2023)
Purpose. The study investigates the current situation of educational research in Colombia, based on the research trends that emerge from the processes developed by universities, groups and lines of research in the country. Method. The methodological design responds to a descriptive content analysis, based on the complementarity perspective, which constitutes a qualitative approach aimed at the holistic understanding of complex cultural realities, based on the analysis of multiple sources of information. Results. The research shows that, despite the multiplicity of research processes in educational sciences, Colombia has not yet consolidated a research structure that enables the generation of disciplinary, interdisciplinary, or transdisciplinary knowledge to promote educational quality and social change in the national territory.